2019
DOI: 10.2528/pierb19010803
|View full text |Cite
|
Sign up to set email alerts
|

Decay Length Estimation of Single-, Two-, and Three-Wire Systems Above Ground Under Hemp Excitation

Abstract: We analytically model single-, two-, and three-wires above ground to determine the decay lengths of common and differential modes induced by an E1 high-altitude electromagnetic pulse (HEMP) excitation. Decay length information is pivotal to determine whether any two nodes in the power grid may be treated as uncoupled. We employ a frequency-domain method based on transmission line theory named ATLOG-Analytic Transmission Line Over Ground to model infinitely long and finite single wires, as well as solve the eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…[2,8,9,23] is appropriate for wires near the ground or buried below the ground. However, we have found that plays a negligible role in aerial lines [13] (which is consistent with the broad applicability of the terminating load capacitance). The external source term for plane wave incidence at oblique angle with respect to z is where .…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…[2,8,9,23] is appropriate for wires near the ground or buried below the ground. However, we have found that plays a negligible role in aerial lines [13] (which is consistent with the broad applicability of the terminating load capacitance). The external source term for plane wave incidence at oblique angle with respect to z is where .…”
Section: Introductionsupporting
confidence: 85%
“…The case with open circuits at both ends of the line is shown in Figure 2(a). The dotted curves have idealized open circuits at the ends of the transmission line, whereas the solid curves have the preceding terminating capacitive loads in (13). Notice that the phase shift caused by the terminating capacitive loads results in alignment of the curves in phase with the full wave simulations given by the The case with short circuits at both ends of the line is shown in Figure 2(b).…”
Section: Comparison Of Full Wave Simulations With Atlog For Open and Short Circuit Terminations Without Radiationmentioning
confidence: 96%
See 2 more Smart Citations